THE POTENTIAL ANTICANCER AND NEPHROPROTECTIVE EFFECTS OF FREE OR NANOPARTICLES ENCAPSULATED SITAGLIPTIN IN MOUSE SOLID EHRLICH CARCINOMA (Journal of Pharmaceutical Negative Results, 2023)
Background: Breast cancer treatment modalities are in persistent need to be modified due to the rising incidence and associated chemotherapeutics resistance and cytotoxicity. The goal of this work was to evaluate any potential anti-cancerous and nephroprotective effects of sitagliptin either its free form or nanoparticles (NPs) encapsulated form on solid Ehrlich carcinoma in mice. It focused on assessment of nephrotoxicity, drug resistance, apoptosis, oxidative stress, proliferation, and angiogenesis.Methods: Breast cancer experimental animal model SEC was induced in female albino mice through the subcutaneous implantation of Ehrlich ascites carcinoma (EAC) cells. Mice were randomly divided into 9groups (n=8). Group1 (normal control), group2 (untreated SEC), group3 (SEC +5-FU), group4 (SEC+ SITA), group5 (SEC +SITA-PLGA), group6 (SEC+SITA-Niosome), group7 (SEC+5FU+SITA), group8 (SEC+5FU+SITA-PLGA) and group9 (SEC+5FU+SITA-Niosome). Tumor volume was recorded and on the 28th day post tumor inoculation, mice were sacrificed, blood samples were collected for the assay of BUN and serum creatinine. Tumor was dissected for the assessment of multi-drug resistance-1 (MDR-1), caspase3؛ the other part was prepared for the histopathological examination and immunohistochemical staining of ki67 and VEGF. Moreover, histopathological examination of renal tissue was done.Results: Administration of sitagliptin augment the anti-cancer properties of 5-FU and showed nephroprotective effects against 5-FU induced nephrotoxicity. Regarding the anticancer effects the nanoparticle formulations of sitagliptin have no significant difference in end tumor volume. however, they showed higher apoptotic properties evidenced by significant increase in the expression of caspase3.Conclusions: Sitagliptin demonstrated nephroprotective effects which evidenced through significant decrease in BUN and serum creatinine levels and histopathological findings. The nephroprotective properties were augmented by loading sitagliptin on either PLGA or Niosome NPs with superiority to the sitagliptin-niosome NPs.